2018
DOI: 10.18203/2394-6040.ijcmph20182183
|View full text |Cite
|
Sign up to set email alerts
|

A community based study of neonatal mortality in Aligarh by using verbal autopsy

Abstract: Background:Neonatal mortality rate is regarded as an important and sensitive indicator of the health status of a community. Children face the highest risk of dying in their first month of life. The present study was aimed to 1) determine the prevalence of neonatal mortality rate 2) identify socio-biological factors in relation to neonatal mortality.3) determine the causes of neonatal mortality. Methods:A community based cross sectional study was conducted in the field practice areas of Department of Community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Numerous studies conducted in India have found birth asphyxia to be a significant cause of newborn death, which is consistent with our study’s findings. [ 4 5 6 7 8 9 10 11 12 13 14 15 ] The lack of sufficient resuscitation care at the time of birth is reflected in the high rate of neonatal mortality caused by birth asphyxia. Unnecessary augmentations of labour and inadequate foetal monitoring during the intranatal period have been considered as contributors of neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies conducted in India have found birth asphyxia to be a significant cause of newborn death, which is consistent with our study’s findings. [ 4 5 6 7 8 9 10 11 12 13 14 15 ] The lack of sufficient resuscitation care at the time of birth is reflected in the high rate of neonatal mortality caused by birth asphyxia. Unnecessary augmentations of labour and inadequate foetal monitoring during the intranatal period have been considered as contributors of neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…20 Baqui et al identified most common cause of death on day zero as birth asphyxia or injury (31%) followed by preterm birth (26%) while on days 1-6, most common cause was preterm birth (30%) followed by sepsis or pneumonia (25%). 21 Also, most common cause of neonatal death was prematurity Chauhan et al, Mengesha et al 22,23 The current study is a hospital-based study relying on records of deaths provided by the hospital, so it cannot be generalized to the larger population. Recall bias may be present since verbal autopsy has not been conducted as soon as the neonate had expired, rather a duration of 6 months has been fixed within which the interview has to be conducted.…”
Section: 3% Lbw With Prematurity Birth Asphyxia Sepsismentioning
confidence: 98%